2023
DOI: 10.1088/1674-1056/acc51f
|View full text |Cite
|
Sign up to set email alerts
|

Probing the effects of lithium doping on structures, properties, and stabilities of magnesium cluster anions

Abstract: Bimetallic clusters aroused tremendous interest because of the property changes that occur: structure, size, and composition. Herein, a structural search of the global minimum for anionic LiMg n – (n=2–11) clusters was performed using an efficient CALYPSO structural searching program with subsequent DFT calculations. A great variety of low energetic isomers converged, and the most stable ones were confirmed by comparing their total energy for each size.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…In addition, the simple harmonic vibration frequency calculations performed along with structural optimization require that no imaginary frequencies appear, ensuring that the obtained states correspond to local minima on the potential energy surface. This choice of calculation level is based on the previous successful studies of Mg-based clusters reported. ,, Note that in all structural optimization calculations, a default convergence criterion of Gaussian 09 was used. The charge transfer characteristics of doped atom and host atom were analyzed through natural bond orbital (NBO) calculations .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the simple harmonic vibration frequency calculations performed along with structural optimization require that no imaginary frequencies appear, ensuring that the obtained states correspond to local minima on the potential energy surface. This choice of calculation level is based on the previous successful studies of Mg-based clusters reported. ,, Note that in all structural optimization calculations, a default convergence criterion of Gaussian 09 was used. The charge transfer characteristics of doped atom and host atom were analyzed through natural bond orbital (NBO) calculations .…”
Section: Methodsmentioning
confidence: 99%
“…This choice of calculation level is based on the previous successful studies of Mg-based clusters reported. 35 , 36 , 52 Note that in all structural optimization calculations, a default convergence criterion of Gaussian 09 was used. The charge transfer characteristics of doped atom and host atom were analyzed through natural bond orbital (NBO) calculations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of theoretical and experimental results subsequently demonstrated the excellent properties of graphene, such as high stability, 2 thermal conductivity, 3 specific surface area 4,5 and electron migration rate, 6 resulting in a wide range of applications in electronic devices, gas sensing devices and other fields. In addition, the electronic properties can be regulated by means of size, 7 strain, 8 doping, 9 defects 10 and stacking through van der Waals (vdW) interactions, 11–13 which greatly broadens the application range of 2D carbon materials. Therefore, with the deepening of graphene research, more researchers are discovering and looking for other new 2D carbon materials.…”
Section: Introductionmentioning
confidence: 99%
“…Doped boron clusters have been the focus of theoretical and experimental studies. 22–26 This is because doping atoms are used to tune the properties and geometry of boron clusters. Mannix et al used 3D metal atom (Co)-doped planar boron clusters (B 18 − ) in order to understand how the dopant affects the properties of pristine boron.…”
Section: Introductionmentioning
confidence: 99%